A Scoping Review of Energy Consumption in Industrial Robotics - Johannes Muru; Anton Rassõlkin (Machines)
The increasing adoption of industrial robots has significantly advanced manufacturing efficiency and flexibility. However, this expansion introduces new energy consumption challenges, especially as electricity has become the dominant energy source in automated systems. As the industrial sector faces rising energy costs and ambitious sustainability goals, understanding and minimizing the energy consumption of robotic systems is imperative. This review presents a structured analysis of energy consumption in industrial robots, linking mechanical design, actuation systems, and control strategies to their energetic effects. We first discuss different industrial robot types and their kinematic configurations, identifying how structural characteristics influence energy use. The article then categorizes energy consumption optimization strategies into software-based and hardware-based approaches. A comparative SWOT analysis highlights the strengths and limitations of each approach. The review also explores emerging trends such as DC microgrid integration. The future directions underline the need for standardized energy assessment frameworks and the development of hybrid optimization strategies that combine the reviewed approaches, suitable for being applied in real-world industrial robot applications. This work provides a comprehensive foundation for establishing best practices in energy consumption optimization for industrial robots.